(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The study identifies decadal landuse and landcover (LULC) changes during 1988-2017 in north-eastern Dhaka conurbation of Bangladesh. Driving forces behind the changes in the study area have also been investigated.In this study, LULC changes were studied using two Landsat sensors. GIS post-processing technique was used for satellite image classification, while an in-depth literature review was conducted to identify the drivers of land cover change. Accuracy for the classified maps ranged from 79percent to 86percent. It was found that agricultural land decreased 47.02 percent while homestead vegetation land cover has increased about 88 percent in the last thirty years (1988-2017).The in-depth analysis result indicates that Dhaka metropolitan area expansion, increased population, internal migration, ongoing housing development projects, and lack of proper landuse and land management implementation are the main drivers of LULC changes in the study area. The development control approach needs to be incorporated into the on-going development projects and activities in the eastern region of greater Dhaka to maintain ecological balance and a green environment of the region. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(2), 2021, P 53-66